Integrating risk minimization planning throughout the clinical development and commercialization lifecycle: an opinion on how drug development could be improved - Morrato EH; Smith MY (Dove Medical Press, 2015)
Elaine H Morrato,1 Meredith Y Smith2 1Colorado School of Public Health, University of Colorado, Anschutz Medical Campus, Aurora, CO, 2EMD Serono, Inc, Rockland, MA, USA Abstract: Pharmaceutical risk minimization programs are now an established requirement in the regulatory landscape. However, pharmaceutical companies have been slow to recognize and embrace the significant potential these programs offer in terms of enhancing trust with health care professionals and patients, and for providing a mechanism for bringing products to the market that might not otherwise have been approved. Pitfalls of the current drug development process include risk minimization programs that are not data driven; missed opportunities to incorporate pragmatic methods and market-based insights, outmoded tools and data sources, lack of rapid evaluative learning to support timely adaption, lack of systematic approaches for patient engagement, and questions on staffing and organizational infrastructure. We propose better integration of risk minimization with clinical drug development and commercialization work streams throughout the product lifecycle. We articulate a vision and propose broad adoption of organizational models for incorporating risk minimization expertise into the drug development process. Three organizational models are discussed and compared: outsource/external vendor, embedded risk management specialist model, and Center of Excellence. Keywords: pharmaceuticals, drug development, risk management, organizational design